PTH-137 Safety and efficacy of simeprevir (SMV) plus PEG-IFN/RBV in treatment-naÏve chronic hepatitis c genotype 1 patients eligible for 12 weeks of treatment. (22nd June 2015) - Foster, GR; Asselah, T; Moreno, C; Sarrazin, C; Gschwantler, M; Craxi, A; Buggisch, P; Ryan, R; Lenz, O; Van Dooren, G; Lonjon-Domanec, I; Schlag, M; et al.
Abstract : Introduction: HPC3014 is a Phase 3, open-label study to assess if response to SMV+Peg-IFN/RBV at Week 2 can allow shortening of treatment to 12 weeks, irrespective of baseline and on-treatment factors. Method: Treatment-naïve chronic HCV G1-infected patients with no-to-moderate fibrosis (METAVIR F0–F2) were recruited. In patients with HCV-RNA <25 IU/mL (detectable/undetectable [Roche COBAS ® Taqman ® lower limit of quantification: 25 IU/mL, lower limit of detection: 15 IU/mL]) at Week 2 and undetectable at Weeks 4 and 8, all treatments were stopped at Week 12 (12-week group). If these criteria were not met, Peg-IFN/RBV was continued to Week 24 (in one case extended to Week 48). Results: 123/163 (76%) patients treated were eligible for the 12-week group (53% male, 92% white, 40%G1a/60%G1b, 76% METAVIR F0/1 and 26/59/15% IL28B CC/CT/TT). Treatment was well tolerated in the 12-week group; all patients completed therapy and none failed on treatment; 33% (41/123) of patients relapsed and 3% (4/123) were lost to follow-up. Grade 3 AEs at least possibly related to SMV were experienced by 5% (6/123) of patients. No grade 4 AEs were considered related to SMV; 3% (4/123) of patients experienced an SAE (considered not related to SMV). AEs of special interest in >10% of patients were pruritus (36%), rash (any type, 17%), neutropenia (20%), dyspnoea (15%) and anaemia (11%). Overall SVR12 in the 12-week group was 66% (81/123) but was higher in patients with IL28B CC genotype (94%), patients with baseline viral load ≤800, 000 IU/mL (82%), those with mild fibrosis (F0–F1) (74%), and those with undetectable HCV-RNA at Week 2 (77%). Amongst patients with undetectable HCV-RNA at Week 2, SVR12 rates still varied based on baseline factors. Conclusion: Week 2 response alone did not predict treatment outcomes as other baseline factors such as IL28B genotype, baseline viral load and fibrosis score seemed to influence SVR rates. Multivariate analyses are ongoing using factors associated with higher SVR rates shown in this analysis in order to create a strong model to select patients with a good chance of SVR after 12 weeks of therapy. Disclosure of interest: G. Foster Conflict with: BMS, Gilead, Janssen, GSK, Roche, Springbank, Tekmira, T. Asselah Conflict with: AbbVie, Janssen, Gilead, BMS, Merck, Roche, C. Moreno Conflict with: AbbVie, Astellas, BMS, Gilead, Janssen, MSD, Roche, C. Sarrazin Conflict with: Abbott, Abbvie, BMS, Gilead, Janssen, Merck/MSD, Qiagen, Roche, Siemens, M. Gschwantler Conflict with: AbbVie, BMS, Gilead, Janssen, MSD, Roche, A. Craxi: None Declared, P. Buggisch Conflict with: AbbVie, BMS, Gilead, Janssen, MSD, Roche, R. Ryan Conflict with: Janssen, O. Lenz Conflict with: Janssen, G. Van Dooren Conflict with: Janssen, I. Lonjon-Domanec Conflict with: Janssen, M. Schlag Conflict with: Janssen, M. Buti Conflict with: Gilead, Janssen, MSD.